2021
DOI: 10.3389/fnut.2021.685165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Leucine Trigger Hypothesis to Explain the Post-prandial Regulation of Muscle Protein Synthesis in Young and Older Adults: A Systematic Review

Abstract: Background: The “leucine trigger” hypothesis was originally conceived to explain the post-prandial regulation of muscle protein synthesis (MPS). This hypothesis implicates the magnitude (amplitude and rate) of post-prandial increase in blood leucine concentrations for regulation of the magnitude of MPS response to an ingested protein source. Recent evidence from experimental studies has challenged this theory, with reports of a disconnect between blood leucine concentration profiles and post-prandial rates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 64 publications
1
43
0
Order By: Relevance
“…This could be explained by the fact that the leucine trigger hypothesis, from whey protein isolate, is insufficient for muscle protein synthesis (MPS) in our study. The leucine trigger hypothesis is because protein administration, especially whey protein isolate, increases blood concentrations of essential amino acids, mainly leucine, and promotes MPS mediated by activation of the target complex of rapamycin 1 (mTORC1) [46,47]. However, there are some considerations that would modify leucine concentration (the dose and source of protein; the type and intensity of exercise), derived from protein supplementation, which could alter MPS [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be explained by the fact that the leucine trigger hypothesis, from whey protein isolate, is insufficient for muscle protein synthesis (MPS) in our study. The leucine trigger hypothesis is because protein administration, especially whey protein isolate, increases blood concentrations of essential amino acids, mainly leucine, and promotes MPS mediated by activation of the target complex of rapamycin 1 (mTORC1) [46,47]. However, there are some considerations that would modify leucine concentration (the dose and source of protein; the type and intensity of exercise), derived from protein supplementation, which could alter MPS [46].…”
Section: Discussionmentioning
confidence: 99%
“…The leucine trigger hypothesis is because protein administration, especially whey protein isolate, increases blood concentrations of essential amino acids, mainly leucine, and promotes MPS mediated by activation of the target complex of rapamycin 1 (mTORC1) [46,47]. However, there are some considerations that would modify leucine concentration (the dose and source of protein; the type and intensity of exercise), derived from protein supplementation, which could alter MPS [46]. Therefore, the differences observed in the groups supplemented with MIPS compared to GC would justify supplementation with MIPS, because MPS would be increased attenuating muscle damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that consuming a protein and leucine-enriched bar -formulated with 16 g of a blend of micellar casein, whey protein, and whey protein hydrolysate -induced aminoacidemia comparable to consuming a single higher-protein-containing meal (0.5g of protein/kg) (Traylor et al 2021). Previous studies also reported that higher leucine-containing proteins enhance MyoPS and whole-body protein synthesis in young and older adults (Glynn et al 2010;Zaromskyte et al 2021). The effect of leucine on daily MyoPS can be independent of daily protein intake (Devries et al 2018a(Devries et al , 2018bMurphy et al 2016).…”
Section: Introductionmentioning
confidence: 91%
“…Overall, beyond differences in intake, our data indicate that the peripheral AA appearance of threonine, methionine, and cysteine, and to a lesser extent, leucine and isoleucine, are dependent on the protein sources in older adults. Although in this study, leucine concentrations were enough to stimulate MPS in healthy older adults based on previous findings [ 96 , 97 ], the remaining IAA (e.g., methionine and threonine), more so than NIAA [ 98 , 99 ], must also be present in adequate concentrations at the same time to act as precursors and allow efficient protein accretion; otherwise, they are referred to as limiting AA [ 100 , 101 ]. Therefore, a delay in and/or insufficient IAA availability, as seen in this and other studies examining plant protein postprandial curves [ 18 , 19 , 23 , 48 , 73 , 74 , 76 ], combined with an ageing effect hindering digestion and absorption [ 84 , 102 ], is expected to have a detrimental impact on the optimal utilisation of all the other AA in the PPF products.…”
Section: Discussionmentioning
confidence: 82%